Investigating BoLA Class II DRB3009:02 carrying cattle in Japan - Fujimori, Sho; Ando, Tatsuya; Sekiguchi, Satoshi; Notsu, Kosuke; Ishida, Shogo; Daidoji, Tomo; Hagiwara, Katsuro (Veterinary and animal science, 2025)
•Retention of the BL resistance gene BoLA Class II DRB3×009:02 in Japanese cattle.•The level of BL resistance gene carriage differed between farmers.•BLV positive rates were low in herds with high levels of BL resistance gene carriage.•BLV prevention measures in areas where BLV is endemic include increasing the production of cattle that carring the BL resistance gene. Enzootic bovine leukosis (EBL) is a malignant lymphoma of cattle that is mainly caused by bovine leukemia virus (BLV) infection. In this study, PCR-RFLP was used to investigate the frequency of the DRB3*009:02 allele in several farms with different herd management practices in Japan. A total of 742 Holsteins (384) and Japanese Blacks (230) were used as the sample size for the study, which was larger than the number of cattle in the study area with a confidence level of 95 % and a margin of error of 8. PBMCs isolated from whole blood from clinically healthy cattle were used for examination. The presence of BLV provirus infection was determined by qPCR targeting the env region. BLV antibodies were detected using a commercial ELISA kit. The results showed that 35 cattle were heterozygous for DRB3*009:02. The frequency on each farm varied between farms, and PCR analysis showed that the prevalence of BLV also varied between farms. The incidence rate (4.7 %) was lower than in previous studies. The BLV seroprevalence (14.4 %) in this study was lower than the BLV infection rate (35 %) in the study. Holstein dairy cows had low levels of BL resistance genes, confirming the spread of the virus within the farm's herd. Cattle on farms with low BLV-positive rates had a resistance gene-carrying rate of 16.9 %, meanwhile, those who did not carry the resistance gene had a rate of 91.4 %. BLV provirus levels vary between farmers, with herds carrying low BL-resistance genes tending to have higher levels of BLV provirus. In light of the current BLV epidemic, herd composition reform, along with aggressive breeding of BL-resistant sires, is a required component to increase the herd of BL-resistant sires and improve livestock productivity. [Display omitted]